Chemical and morphological characteristics of common bean seed and evaluating genetic advance in commercial classes - Aziziaram, Zahra; Cheghamirza, Kianoosh; Zarei, Leila; Beheshti-Alagha, Ali (Cellular and Molecular Biology, 2022)
Common bean (Phaseolus vulagris L.) is a nutritionally important food crop with prospective health benefits in the world. The current study was evaluated the chemical components, morphological characteristics, and genetic advance of 22 common bean cultivars/lines seeds from three commercial classes (white, red, pinto beans) adapted to different climates of Iran. The results showed significant variations among 22 common bean cultivars/lines for all studied seed traits. The commercial group comparisons showed that pinto beans were the best in terms of seed morphological characteristics but red beans were superior for seed protein percentage and zinc content. White beans had high amounts of iron, calcium and magnesium, and also presented high amounts of starch and uronic acid as anti-nutritional factors. Among the chemical components, crude fat had the highest genetic and phenotypic coefficients of variation, whereas starch percentage showed the lowest values. The genetic advance over the mean ranged from 6.73% (starch percentage) to 66.31% (100-seed weight), and high heritability was estimated for calcium content (0.99). AND1007 Line demonstrated the high seed protein, iron and zinc contents. To confirm the results, a genotype-by-trait biplot was done. These results could help to achieve a common bean cultivar with a high amount of nutritional value of seeds and appropriate seed characteristics with a low amount of anti-nutritional factors.